Efficient synthesis of 2,5-dicarbonyl derivatives of 3,4-ethylenedithiothiophene (EDTT) via addition-elimination reaction - Al-jumaili, Mustafa A-jabbar; Woodward, Simon (Elsevier, 2017)
Derivatives of 3,4-ethylenedithiothiophene (EDTT) are reported starting from tetrabromothiophene. Selective 2,5-dilithiation followed by reaction with a range of aldehydes gives diols as mixtures of diastereomers. Only the 2 and 5 positions in thiophene react leaving the 3,4-bromides for further elaboration. The diols are oxidised to their corresponding diketones using activated MnO2. Reaction with 1,2-ethanedithiol, by addition-elimination, provides access to novel monomers for the preparation of conjugated copolymers of 3,4-ethylenedithiothiophene (EDTT). A range of these monomers can be attained by applying the synthesis of a series of ketones applicable to further synthesis of π-extended thiophene-based organic semiconductors. Finally, this new route was compared to 3,4-ethylenedioxythiophene (EDOT) dialdehyde derivatives synthesised by an alternative to literature chemistry.